Ketahanan Varietas/Klon Ubikayu Umur Genjah terhadap Tungau Merah - Indiati, S. W. (Jurnal Penelitian Pertanian Tanaman Pangan, 2012)
Pest and diseases are major constraints to crop production. The red spider mite is an important pest of cassava, particularly in the dry regions. The use of tolerant cassava varieties is considered an effective control technique. which does not pollute the environment. A study was carried out to identify the tolerance of 15 cassava varieties/clones to red spider mites and characterize the resistance to the pest in the dry land. Experiments were conducted in a greenhouse and in farmersÂ’ fields during the dry season of 2009. Each of the trial was arranged in a randomized block design with 15 cassava clones as treatments in three replications. The results showed that clones/varieties OMM 9076, Adira 1, M4-p, Malang 6, and Adira-4 were tolerant to the red spider mites. At a condition of severe pest infestation, none of clones/varieties was tolerant to the pest. Differences in tolerance appeared only on the length of incubation time until appearance of the pest symptoms. Cassava clones/varieties were more tolerant, when the pest symptom appeared later than on the susceptible ones. Clone CMM 03094-12 had the highest leaf numbers per plant, while clone M4-p, variety Adira 1, and clone OMM 9076 had leaf water content more than 70%. There was a tendency of low levels of mites attack on clones/varieties with leaf water contents more than 70%. When the cassava crops were harvested at 7 months old, Clone OMM 9076 produced the highest yield (28 t/ha) on the uncontrolled and 32 t/ha on the controlled plot. Clone OMM 9076 was considered as a high yielding and early maturing genotype.